2014
DOI: 10.1007/s12550-014-0217-z
|View full text |Cite
|
Sign up to set email alerts
|

First results on citrinin biomarkers in urines from rural and urban cohorts in Bangladesh

Abstract: Citrinin (CIT) is a mycotoxin contaminant in food commodities and can co-occur with ochratoxin A (OTA), another nephrotoxic contaminant in food and feed. Presence of OTA in maize from Bangladesh has been reported, but no data exist on CIT occurrence in food or feed in Bangladesh. Since biomonitoring provides the best approach to assess human exposure to contaminants from various sources and by all routes, a validated method for biomarker analysis has been used to investigate the presence of CIT and its metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…CIT is excreted in urine as such and as OHCIT in above 70% of the subject studied (Blaszkewicz et al, 2013;Ali et al, 2015a;Ali et al, 2015b), either adults and children (Blaszkewicz et al, 2013). In the available dataset, there are 9 works of which 3 papers investigated CIT and CIT metabolite, dihydrocitrinone (OHCIT), while 6 publications have introduced CIT in a multi-mycotoxin study.…”
Section: Citrinin and Tenuazonic Acidmentioning
confidence: 99%
“…CIT is excreted in urine as such and as OHCIT in above 70% of the subject studied (Blaszkewicz et al, 2013;Ali et al, 2015a;Ali et al, 2015b), either adults and children (Blaszkewicz et al, 2013). In the available dataset, there are 9 works of which 3 papers investigated CIT and CIT metabolite, dihydrocitrinone (OHCIT), while 6 publications have introduced CIT in a multi-mycotoxin study.…”
Section: Citrinin and Tenuazonic Acidmentioning
confidence: 99%
“…Recent studies have shown the co-occurrence of CIT and OTA up to 97% in urines of the Bangladeshi adult populations and their urinary concentration for these two biomarkers were often higher than those found in several European studies. 4,9,60,61 Another study reported the frequent occurrence of OTA in blood plasma of adult students in Bangladesh. 14…”
Section: Occurrence Of Cit and Ota In Humans In Asiamentioning
confidence: 99%
“…Samples from Bangladesh (n=95) were collected from residents of rural and urban areas of Rajshahi District (Ali et al 2015c). Samples from Germany (n=50) were collected in the area of the city of Dortmund.…”
Section: Sample Collection and Originmentioning
confidence: 99%